Protective Effects of Dioscin against Lipopolysaccharide-Induced Acute Lung Injury through Inhibition of Oxidative Stress and Inflammation - Yao, Hong; Sun, Yiping; Song, Shasha; Qi, Yan; Tao, Xufeng; Xu, Lina; Yin, Lianhong; Han, Xu; Xu, Youwei; Li, Hua; Sun, Huijun; Peng, Jinyong (Frontiers in Pharmacology, 2017)
The protective effects of dioscin, a natural steroidal saponin from some medicinal plants including Dioscorea nipponica Makino, against lipopolysaccharide (LPS)- induced acute liver and renal damages have been reported in our previous works. However, its effect on LPS-induced acute lung injury (ALI) remains unknown. In the present study, the effects and possible mechanisms of dioscin against LPS-induced ALI in vitro and in vivo were investigated. The results showed that dioscin effectively inhibited cell proliferation and markedly decreased reactive oxidative species (ROS) level in 16HBE cells treated by LPS. In addition, dioscin significantly attenuated LPS-induced histological alterations, suppressed the infiltration of inflammatory cells, as well as decreased the levels of MDA, SOD, NO and iNOS in mice and rats (p < 0.05). Mechanistically, dioscin significantly decreased the protein levels of TLR4, MyD88, TRAF6, TKB1, TRAF3, phosphorylation levels of PI3K, Akt, IκBα, NF-κB, and the mRNA levels of IL-1β, IL-6 and TNF-α against oxidative stress and inflammation (p < 0.05). TLR4 overexpression was also decreased by dioscin, leading to the markedly decreased the levels of MyD88, TRAF6, TKB1, TRAF3, p-PI3K, p-Akt, p-IκBα and p-NF-κB. These findings provide new insights that dioscin exhibited protective effect against LPS-induced ALI via adjusting TLR4/MyD88- mediated oxidative stress and inflammation, which should be developed as one potent candidate for the treatment of ALI in the future.